Focal and generalized seizure activity after local hippocampal or cortical ablation of NaV1.1 channels in mice. (19th March 2020) - Jansen, Nico A.; Dehghani, Anisa; Breukel, Cor; Tolner, Else A.; van den Maagdenberg, Arn M. J. M.
Abstract: Early onset seizures are a hallmark of Dravet syndrome. Previous studies in rodent models have shown that the epileptic phenotype is caused by loss‐of‐function of voltage‐gated NaV 1.1 sodium channels, which are chiefly expressed in γ‐aminobutyric acid (GABA)ergic neurons. Recently, a possibly critical role has been attributed to the hippocampus in the seizure phenotype, as local hippocampal ablation of NaV 1.1 channels decreased the threshold for hyperthermia‐induced seizures. However, the effect of ablation of NaV 1.1 channels restricted to cortical sites has not been tested. Here we studied local field potential (LFP) and behavior in mice following local hippocampal and cortical ablation of Scn1a, a gene encoding the α1 subunit of NaV 1.1 channels, and we compared seizure characteristics with those of heterozygous global knockout Scn1 ‐/+ mice. We found a high incidence of spontaneous seizures following either local hippocampal or cortical ablation, notably during a transient time window, similar to Scn1a ‐/+ mice. Nonconvulsive seizure activity in the injected area was common and preceded generalized seizures. Moreover, mice were susceptible to hyperthermia‐induced seizures. In conclusion, local ablation of NaV 1.1 channels in the hippocampus and cortex results in focal seizure activity that can generalize. These data indicate that spontaneous epileptic activity may initiate in multiple brain regions in Dravet syndrome.